The Effectiveness of Chemical Cautery and Electrosurgery on Anogenital Wart: Systematic Review - Mawardi P; Kamilah L; Fauziyyah Heryadi F; Arrosyid A (Clinical, Cosmetic and Investigational Dermatology, 2023)
Prasetyadi Mawardi, Lian Kamilah, Fanny Fauziyyah Heryadi, Azhar Arrosyid Department of Dermatology and Venereology, Faculty of Medicine, Sebelas Maret University/Dr Moewardi General Hospital, Surakarta, IndonesiaCorrespondence: Prasetyadi Mawardi, Department of Dermatology and Venereology, Faculty of Medicine, Sebelas Maret University/Dr Moewardi General Hospital, Surakarta, Central Java, Indonesia, Tel +6281229750211, Email prasetyadi_m@staff.uns.ac.idIntroduction: Anogenital warts (AGW) is one of the sexually transmitted infections (STIs) caused by human papillomavirus (HPV). Treatment modalities of AGW yield low clearance and recurrence rate, so that chemical cautery with trichloroacetic acid (TCA) and electrosurgery are widely used to remove the lesions without any severe side effects.Objective: To investigate the efficacy of chemical cautery with TCA and electrosurgery in AGW based on clinical trials or case series.Methods: The systematic review was reported according to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) but not registered to the International Prospective Register of Systematic Review (PROSPERO). To acquire proper and accurate information from relevant literature, two databases PubMed and the Cochrane Library were searched from January 2013 to March 2023.Results: Thirteen studies were included in this systematic review, comprising seven articles on chemical cautery and six electrosurgery articles. The highest cure rate of chemical cautery with TCA was 94.1% while electrosurgery was 100%. A relatively low recurrence rate during 1 year follow-up was observed in electrosurgery with 14.6%, whereas the chemical cautery was 27.6%.Conclusion: Electrosurgery for AGW treatment had higher cure rate with lower recurrence rate compared to chemical cautery with TCA. Numerous adverse effects of electrosurgery were reported include bleeding and scar formation as high risk of HPV infection.Keywords: anogenital warts, chemical cautery, electro cautery, electrosurgery, trichloroacetic acid